Sorghum Development in Indonesia: Market Efficiency and Partnership Model Approach - Widodo, Sugeng; Sulistyawati Purwaning Rahayu, Heni; Laksono, Pandu; Fahmi, Diah Arina; Triastono, Joko; Sahara, Dewi; Kristamtini; Sutardi; Budi Pustika, Arlyna; Widyayanti, Setyorini; Muazam, Arif; Purwaningsih, Heni (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Sorghum is a drought-tolerant crop that can contribute to Indonesia’s food security and income generation. However, this potential often fails to improve farmers’ income and welfare unless accompanied by economic feasibility, particularly in marketing practices. This study examined market efficiency and partnership models in sorghum development in Daerah Istimewa Yogyakarta and Central Java Provinces. The research analyzed the marketing cost, marketing margin, farmers’ share, and partnership cultivation models of the sorghum. The data were collected through surveys, interviews, and observations to 120 sorghum farmers and 60 traders. The study utilized descriptive statistics, ANOVA to compare farmers’ share in the different marketing channels, and the Analytic Hierarchy Process (AHP) to select the partnership models. The results unveiled Channel II which consisting of farmers, village collector traders, traders outside the city or regency, and national companies, produced the highest marketing margin. Meanwhile, Channel III, comprising farmers, village collector traders, and the local feed industry, generated the highest farmers’ share. The study revealed that sole proprietorship partnerships were the farmers' dominant choice in the sorghum business. Nevertheless, the partnership model with feed industry had also formed in the research area.